3x-4x=12 that means -x equals 12 so x equals -12
3x + 4y = 12 Subtract 3x from each side 4y = 12 - 3x Divide by 4 on each side y = 3 - .75x The slope is what is multiplied by "x" or -.75
x = 4 and y = 0
3x - 4y = 10-3x - 4y = 8 -> add line 1 to line 2 3x - 4y = 100x - 8y = 18 -> -8y = 18 -> y = -18/8 = -9/4 -> 3x - 4*(-9/4) = 10 -> 3x + 9 = 10 -> 3x = 1 -> x = 1/3
Move everything except the y to the same side as 12 to put the answer in slope-intercept form. -4y=-3x+12 y=3/4x -3
3x-4x=12 that means -x equals 12 so x equals -12
3x + 4y = 12 Subtract 3x from each side 4y = 12 - 3x Divide by 4 on each side y = 3 - .75x The slope is what is multiplied by "x" or -.75
They are two regions of the Cartesian plane with the straight line 3x + 4y = 12 defining their boundary. That line is not part of either region.
(0,-4)
We cannot say anything because the value of x and y can be any thing. if x and y are 4,0 or 0,3 respectively then it is equal.But u can find many such values for 3x+4y=12.there are infinite values for 3x+4y<12 and 3x+4y>12
3x=4y-x 4x=4y x=y
-3x + 4y = 12 Temporary value of y: 4y = 3x + 12 y = (3x + 12) / 4 Substituting y: -3x + 4 [(3x+12) / 4] = 12 -3x + 12x + 48 = 12 -3x + 12x = 12 - 48 9x = 12 - 48 9x = -36 x = -36 / 9 x = -4 Subtituting x to get the final value of y: -3(-4) + 4y = 12 12 + 4y = 12 4y = 12 - 12 4y = 0 y = 0 Final answer: x = -4 y = 0 Check: -3x + 4y = 12 -3(-4) + 4(0) = 12 12 + 0 = 12 12 = 12 Solution 2: -3x + 4y = 12 Temporay value of x: 3x = 4y - 12 x = (4y - 12) / 3 Substituting x to get the value of y: 3[(4y - 12) / 3] + 4y = 12 12y - 36 + 4y = 12 16y = 12 + 36 16y = 48 y = 48 / 16 y = 3 Substituting y to get the value of x: -3x + 4(3) = 12 -3x + 12 = 12 -3x = 12 - 12 x = 0 Final Answer: x = 0 y = 3 Check: -3(0) + 4(3) = 12 12 = 12
x = 4 and y = 0
plot 4y then 3x
x = - 4 and y = 0
4y= -3x + 12 y = -3/4x + 3 The perpendicular slope is 4/3
3x - 4y = 10-3x - 4y = 8 -> add line 1 to line 2 3x - 4y = 100x - 8y = 18 -> -8y = 18 -> y = -18/8 = -9/4 -> 3x - 4*(-9/4) = 10 -> 3x + 9 = 10 -> 3x = 1 -> x = 1/3